Rhetoric, Reality, and Reputation: Do CSR and Political Lobbying Protect Shareholder Wealth against Environmental Lawsuits? - Liu, Chelsea; Cheong, Chee Seng; Zurbruegg, Ralf (Journal of financial and quantitative analysis, 2020)
We investigate whether firms' corporate social responsibility (CSR) reputations and environmental lobbying efforts protect shareholder wealth in the event of environmental lawsuits. Using a sample of lawsuits filed in United States Federal Courts, we find that firms with superior CSR reputations suffer worse market reactions to environmental allegations. In contrast, lobbying cushions filing-date valuation losses, providing insurance-like protection against lawsuits. Our results are robust to subsample analyses, a falsification test, propensity score matching, and alternative empirical proxies and model specifications.